Regioselective hydrothiolation of terminal acetylene catalyzed by magnetite (Fe3O4) nanoparticles. Issue 4 (16th February 2017) - Rocha, Manuela S. T.; Rafique, Jamal; Saba, Sumbal; Azeredo, Juliano B.; Back, Davi; Godoi, Marcelo; Braga, Antonio L.
ABSTRACT: Herein, we report a new and solvent-free methodology for the preparation of vinyl thioethers from terminal alkynes and thiols, using magnetite (Fe3 O4 ) nanoparticles as a recyclable catalyst. With this greener method, the desired vinyl thioethers were achieved in good yields and with good stereoselectivity. In addition, the catalyst was easily recovered using a simple external magnet and reused for further catalytic reactions without significant loss of activity up to the fifth cycle. GRAPHICAL ABSTRACT: